2021
DOI: 10.9734/jpri/2021/v33i38a32069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HRCT chest in COVID-19 Pneumonia

Abstract: COVID-19 pneumonia is a recently identified lung infection, the hazardous factor of this pneumonia is pandemic dissemination of infection by corona virus. Due to its high mortality and morbidity it has become a threat to the human life. As pneumonia is the commonest manifestation chest x-ray becomes the primary modality of investigation however many symptomatic patients do not have a positive chest X-ray findings hence, HRCT is used as primary modality for both screening as well as a diagnosing COVID-19 pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A subdural empyema develops as a result of septic thrombophlebitis of the mucosal sinus veins, which causes retrograde infection extension with bacterial drainage into the dural venous sinuses and cortical veins. Subdural empyema can also develop as a side effect of head trauma, from an infection of a subdural effusion, or from a direct infection of the subdural space occurring during a neurosurgical procedure like draining a subdural hematoma [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A subdural empyema develops as a result of septic thrombophlebitis of the mucosal sinus veins, which causes retrograde infection extension with bacterial drainage into the dural venous sinuses and cortical veins. Subdural empyema can also develop as a side effect of head trauma, from an infection of a subdural effusion, or from a direct infection of the subdural space occurring during a neurosurgical procedure like draining a subdural hematoma [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough examination of the literature revealed that there are several research that show education had significant effect in improving the knowledge regarding bone density investigation and its importance and there by contributing in providing knowledge regarding the investigation and importance . This study represented a small effort to educate premenopausal women about low bone density research and its significance [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…'s genetic variations affect how it affects the brain. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The National Neuro AIDS Tissue Consortium is a Project that NINDS and NIMH are both fundings.…”
Section: Discussionmentioning
confidence: 99%